2004
DOI: 10.1097/00006231-200409000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of 2-[18F]fluoro-2-deoxy-D-glucose in uterine leiomyoma: imaging of four patients by coincidence positron emission tomography

Abstract: Uterine leiomyomas, benign tumours of the human uterus, are the most common uterine neoplasm and are composed of smooth muscle with varying amounts of fibrous connective tissue. As a functional imaging modality, 2-[F]fluoro-2-deoxy-D-glucose (F-FDG) positron emission tomography can be used to obtain information about glucose metabolism in tissues. In this study, the findings of the F-FDG scans of four patients who were suspected of having malignant gynaecological tumours because of clinical and radiological fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…In general, SUV values for leiomyosarcoma were observed to be significantly greater than those for leiomyoma. However, numerous reports for 18-FDG-avid leiomyoma were also identified (36)(37)(38). Furthermore, a series of comprehensive analyses for those patients who underwent 18-FDG-PET/CT revealed that small proportion of benign uterine leiomyomas exhibited positive 18-FDG uptake.…”
Section: Discussionmentioning
confidence: 99%
“…In general, SUV values for leiomyosarcoma were observed to be significantly greater than those for leiomyoma. However, numerous reports for 18-FDG-avid leiomyoma were also identified (36)(37)(38). Furthermore, a series of comprehensive analyses for those patients who underwent 18-FDG-PET/CT revealed that small proportion of benign uterine leiomyomas exhibited positive 18-FDG uptake.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been several reports of PET-positive leiomyomas [22][23][24]. Absent FDG-PET avidity was a preoperative sign that this was a benign tumor, especially as a heterogeneous adrenal tumor on CT imaging is likely to be a high-grade carcinoma that would be expected to be FDG-PET positive [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FDG uptake in uterine leiomyoma declines with age [37]. But there are some case reports of intense FDG uptake in large or degenerated benign leiomyomas [36,[38][39][40][41]. Reported high uptake in the leiomyomas might be owing to increased vascularity [40] or large sizes of the tumors [41].…”
Section: Endometrial Uptakementioning
confidence: 99%
“…Reported high uptake in the leiomyomas might be owing to increased vascularity [40] or large sizes of the tumors [41]. In addition, high levels of growth factors and receptors related to proliferation of smooth muscle may play a role in FDG accumulation [38]. Therefore, nonmenstrual-related endometrial uptake may represent either benign or malignant process.…”
Section: Endometrial Uptakementioning
confidence: 99%